Remdesivir Strongly Binds to RNA-Dependent RNA Polymerase, Membrane Protein, and Main Protease of SARS-CoV-2: Indication From Molecular Modeling and Simulations - Khan, Faez Iqbal; Kang, Tongzhou; Ali, Haider; Lai, Dakun (Frontiers in Pharmacology, 2021)
Development of new drugs is a time taking and expensive process. Comprehensive efforts are being made globally towards the search of therapeutics against SARS-CoV-2. Several drugs such as remdesivir, favipiravir, ritonavir, and lopinavir have been included in the treatment regimen and shown effective results in several cases. Among the existing broad-spectrum antiviral drugs remdesivir is found to be more effective against SARS-CoV-2. Remdesivir has broad-spectrum antiviral action against many single-stranded RNA viruses including pathogenic SARS-CoV and Middle East respiratory syndrome coronavirus (MERS-CoV). In this study, we proposed that remdesivir strongly binds to membrane protein, RNA-Dependent RNA Polymerase (RDRP) and Main Protease of SARS-CoV-2. It might show antiviral activity by inhibiting more than one target. It has been found that remdesivir binds to Mprotease, Mprotein, and RDRP with -7.8 kcal/mol, -7.4 kcal/mol, and -7.1 kcal/mol, respectively. The structure dynamics study suggested that binding of remdesivir leads to unfolding of RDRP. It has been found that strong binding of remdesivir to Mprotein leads to decrease in structural deviations and gyrations. Additionally, the average solvent accessible surface area of Mprotein decreases from 127.17 nm2 to 112.12 nm2, respectively. Furthermore, the eigenvalues and the trace of covariance matrix were found to be low in case of Mprotease-remdesivir, Mprotein-remdesivir, and RDRP-remdesivir. The binding of remdesivir to Mprotease, Mprotein, and RDRP reduces the average motions in protein due to its strong binding. The MMPBSA calculations suggested that the average van der Waal energy was highest in case of Mprotease-remdesivir (-298.85 kJ/mol), and the average binding energy was highest in Mprotein-remdesivir (-454.69 kJ/mol). The detailed analysis suggested that remdesivir have more than one target of SARS-CoV-2.